Finding the way forward - Gordon, Jean; McGeoch, Moira; Stewart, Audrey (The Journal of Practice Teaching and Learning, 2012)
Locating sufficient student practice learning opportunities (PLOs) has been a long-standing challenge in social work education. This article highlights key findings of a study carried out in the West of Scotland to inform a move from a reactive approach to regular crises in PLO provision towards the development of a long term strategic plan for social work practice learning in the region. The study involved a combination of methods, including literature review, local audit, focus groups and consultation with individuals and organisations in the West of Scotland and the rest of the UK. The study found local and national evidence of innovation in developing new models of practice learning to meet the demands of 21st Century social work in Scotland as well as a growing concern that an emphasis on finding sufficient PLOs should not compromise the quality of the learning opportunities available to social work students. Some of the study’s implications for practice learning in the West of Scotland and further afield are explored.